Body mass index increase: a risk factor for forced expiratory volume in 1 s decline for overweight and obese adults with asthma. Issue 4 (24th October 2022) - Bermúdez Barón, Nicolás; Kankaanranta, Hannu; Hedman, Linnea; Andersson, Martin; Stridsman, Caroline; Lindberg, Anne; Rönmark, Eva; Backman, Helena
Background: With increasing prevalence of overweight and obesity, it is important to study how body mass index (BMI) change may affect lung function among subjects with asthma. There are few prospective studies on this topic, especially with separate analyses of those with normal and high BMI. The aim of the present study was to prospectively study the association between annual BMI change and annual lung function decline, separately among those with normal initial BMI and overweight/obesity, in an adult asthma cohort. Methods: A population-based adult asthma cohort was examined at study entry between 1986 and 2001 and at follow-up between 2012 and 2014 (n=945). Annual BMI change was analysed in association with annual decline in forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and FEV1 /FVC separately in those with normal weight (BMI 18.5–24.9) and overweight/obese subjects (BMI ≥25) at study entry. Regression models were used to adjust for sex, age, smoking, inhaled corticosteroids use and occupational exposure to gas, dust or fumes. Results: Overweight/obese subjects had lower FEV1 and FVC but slower annual FEV1 and FVC decline compared to those with normal weight. After adjustment through regression modelling, the association between BMI change with FEV1 and FVC decline remained significant for both BMI groups, but with stronger associations among the overweight/obese (FEV1 B[Overweight/obese] =−25 mL versus B[normal weight] =−15 mL). However, when including only those with BMI increase during follow-up, the associations remained significant among those with overweight/obesity, but not in the normal-weight group. No associations were seen for FEV1 /FVC. Conclusions: BMI increase is associated with faster FEV1 and FVC decline among overweight and obese adults with asthma in comparison with their normal-weight counterparts. BMI increase is associated with faster FEV1 and FVC decline in adults with asthma, and this association is stronger among overweight and obese adults with asthma than among their normal-weight counterparts https://bit.ly/3PDxOk0